Properties of paper manufactured from kenaf as function of alkaline pH medium and retention of precipitated calcium carbonate - Mohamed @ Asa'ari, Ainun Zuriyati; Nordin, Nurul Izzati; Suod, Zaida; Abdullah, Hazwani Husna; Jasmani, Latifah (Universiti Putra Malaysia Press, 2017)
The objective of this study was to have a better understanding of the effect of alkaline pH medium in the retention of filler in papermaking using kenaf bleached pulp. Three stages of experiments were carried out involving papermaking at alkaline pH medium 8 to 13, usage of precipitated calcium carbonate (PCC), Albacar (ABC) of needle-shaped and Albafil (ABF) of circular-shaped, and the application of low and high molecular weight of polyacrylamides (PAM LM and PAM HM). Paper samples were manufactured based on TAPPI Test Method T295 om-88. Characterisation of specimens in terms of filler content, tensile, tear and burst strength were carried out. The results showed that pH medium influenced the inter-fibre bonding of the fibres during papermaking whereby pH 8-9 is found as the best medium in producing stronger paper. The findings are significant in order to suit the pH according to certain shape and size of such fillers.